First snake record from the Sarmiento Formation at La Gran Hondonada (Chubut province, Argentina) - Albino, Adriana Maria (2012)
The described indeterminate boid snake was collected in rocks belonging to the Sarmiento Formation and exposed at La Gran Hondonada (Chubut Province, Argentina). This is the first snake record for the mid-late Eocene Mustersan South American land-mammal age. The specimen proves that medium- to large-sized boids inhabited the Patagonian region during most of the Palaeogene, suggesting climatic conditions warmer than those established at the beginning of the Neogene.